2011
DOI: 10.1002/ajpa.21536
|View full text |Cite
|
Sign up to set email alerts
|

Hiding inequality beneath prosperity: Patterns of cranial injury in middle period San Pedro de Atacama, Northern Chile

Abstract: The Middle Period in San Pedro de Atacama (AD 400-1000) stands out as a time of great prosperity that was, in part, associated with high levels of interaction with foreign polities, including the highland state of Tiwanaku. Although previous studies have demonstrated an increase in rates of violence during the subsequent Regional Developments Period (AD 1000-1400), this does not mean that the Middle Period was a time of peace and tranquility. Here, the prevalence of violence in four contemporary cemeteries is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 36 publications
3
39
1
6
Order By: Relevance
“…Cranial modification is an ascribed symbol of group identity and a permanent signifier of social identity imposed upon children; it reflects a decision made by community members and likely represents Wiessner's (1983) emblemic style. In the Andes, modified head shapes appear to be culturally dictated and related to community identities (Blom 2005;Cocilovo and Zavattieri 1994;Torres-Rouff 2002). This cross-generational symbolic decision serves as a relatively stable cultural feature, ideal for analyses of community identity and social change.…”
Section: Community Identities Through Cranial Vault Modificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Cranial modification is an ascribed symbol of group identity and a permanent signifier of social identity imposed upon children; it reflects a decision made by community members and likely represents Wiessner's (1983) emblemic style. In the Andes, modified head shapes appear to be culturally dictated and related to community identities (Blom 2005;Cocilovo and Zavattieri 1994;Torres-Rouff 2002). This cross-generational symbolic decision serves as a relatively stable cultural feature, ideal for analyses of community identity and social change.…”
Section: Community Identities Through Cranial Vault Modificationmentioning
confidence: 99%
“…Analysis of skeletal and dental metric and nonmetric traits affords a view into the relatedness and diversity of different mortuary populations and has been particularly useful in studies of ethnogenesis-the formation of new ethnic groups (Stojanowski 2005;Sutter 2009). Studies of body modifications are important in understanding both intentional signifiers of community identities (e.g., Blom 2005;Tiesler 2014;Torres-Rouff 2008) and unintentional skeletal and dental changes that can then be related to different social identities (Torres-Rouff 2011b). Similarly, biogeochemical studies of paleomobility can be used to infer geographic origins as they relate to social identities (e.g., Knudson and Blom 2009).…”
Section: An Integrated Multiscalar Bioarchaeological Approach To Idenmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the evidence of differential susceptibility to stress and divergent health outcomes within (Hubbe et al 2012) and between (Torres-Rouff 2011) cemeteries, in concert with settlement pattern analyses (Llagostera and Costa 1999), researchers have argued that the Middle Period in the Atacama oases witnessed the strengthening of a local elite who controlled systems of access to distant resources (Llagostera 1996(Llagostera , 2004Núñez 1991Núñez , 2007. Our recent research has indicated that differences within cemeteries in the region strongly reflect social dynamics in the oases (Hubbe et al 2012;TorresRouff et al 2015); thereby motivating an analytical shift from an exclusive focus on comparing sites to a perspective that also incorporates detailed examination of patterns of individual variation within sites and cemeteries.…”
Section: Discussionmentioning
confidence: 99%